NEW INVESTIGATIONS OR RECENT VERTICAL MOVEMENTS IN THE CARPATHO-BALKAN REGION - Joó I.; Füry M.; Arabadžijski D.; Mladenovski M.M.; Meščerskij I.N.; Mihǎila M.; Németh Z.; Thury J.; Steinberg J.; Vanko J.; Wyrzykowski T. (My University, 1987)
Recent work concerning the investigation of vertical movements in the Carpatho-Balkan Region is reported, based on the “Explanatory Text to the Map of Recent Vertical Movements in the Carpatho-Balkan Region”.For this investigation, the following countries supplied information: Bulgaria, Czechoslovakia, GDR, Hungary, Poland, Romania, USSR, Austria, and Italy. The activities were coordinated by the Hungarian Geodetic Service. Hungary undertook the task of collecting the data, their preparation for adjustment, and the adjustment of the investigation network, as well as the compilation and publication of the map of vertical movement. The authors present the algorithm of the rigorous adjustment: the height differences of the second leveling have been adjusted jointly with the velocities derived from the first and second levelings.In this paper the applied geodetic and oceanographic data, as well as the main character of the investigation network are presented. The interpretation of the adjustment is outlined.The map of Recent Vertical Movements in the Carpatho-Balkan Region (CBR) is printed at the scale of 1:1,000,000.In general, it is claimed that due to the new methods of investigation, the new CBR map of vertical movements provides a better tool to help with further investigations.